The Silent Epidemic: Unpacking Cybersecurity Threats in Connected Healthcare Devices (IoMT) - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The healthcare sector is undergoing a profound transformation, driven by the rapid integration of the Internet of Medical Things IoMT. These connected techno...
Keywords: Digital Health; Diagnostics; Healthcare Innovation; Patient Care; Precision Medicine